Pengaruh Kompres Hangat Bawang Merah Terhadap Penurunan Skala Nyeri Punggung Bawah Pada Nelayan - Ni Made Mitha Pratiwi Mitha Pratiwi; I Ketut Andika Priastana; Yohanes Zenriano Tarigan (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2025)
ABSTRACT Introduction: Low back pain or commonly called Low Back Pain (LBP) is one of the health problems that is often experienced due to frequent or repetitive physical activity. One of the non-pharmacological interventions that can help reduce low back pain is a warm compress of shallots, the warmth produced by shallots increases blood vessel flow so that tense muscles relax. Methods: This study used a pre-experimental design with a one group pretest-posttest approach. The population in this study were all fishermen in the work area of UPTD Puskesmas II Negara. A total of 57 respondents were selected using qouta sampling technique. The intervention was carried out by giving warm onion compresses with a time of 20 minutes per session given for 5 consecutive days. The pain scale was measured before and after the intervention using the NRS pain scale observation sheet. Data were analyzed using the Wilcoxon Signed Rank Test. Results: Before the intervention, most respondents experienced moderate to severe pain. After giving warm onion compress, there was a significant decrease in pain levels. The Wilcoxon test shows a value of Z = -7.421 with P < 0.001, which means there is a significant difference between pain before and after the intervention. Discussion: The results showed that the intervention of warm onion compress was effective in reducing low back pain in fishermen. Further research with a control group is recommended to strengthen the results. Keywords: Warm compress, shallots, fishermen, low back pain, non-pharmacological therapy